The Immunogenicity and Immune Tolerance of Pluripotent Stem Cell Derivatives - Liu, Xin; Li, Wenjuan; Fu, Xuemei; Xu, Yang (Frontiers in Immunology, 2017)
Human embryonic stem cells (hESCs) can undergo unlimited self-renewal and differentiate into all cell types in human body, and therefore, hold great potential for cell therapy of currently incurable diseases including neural degenerative diseases, heart failure and macular degeneration. This potential is further underscored by the promising safety and efficacy data from the ongoing clinical trials of hESC-based therapy of macular degeneration. However, one main challenge for the clinical application of hESC-based therapy is the allogeneic immune rejection of hESC-derived cells by the recipient. The breakthrough of the technology to generate autologous induced pluripotent stem cells (iPSCs) by nuclear reprogramming of patient's somatic cells raised the possibility that autologous iPSC-derived cells can be transplanted into the patients without the concern of immune rejection. However, accumulating data indicate that certain iPSC-derived cells can be immunogenic. In addition, the genomic instability associated with iPSCs raises additional safety concern to use iPSC-derived cells in human cell therapy. In this review, we will discuss the mechanism underlying the immunogenicity of the pluripotent stem cells and recent progress in developing immune tolerance strategies of hESC-derived allografts. The successful development of safe and effective immune tolerance strategy will greatly facilitate the clinical development of hESC-based cell therapy.